Do able managers take more risks? - Lingsha Cheng; Yongmin Zhang (Journal of Innovation & Knowledge (JIK), 2022)
Empirical evidence on the relation between managers and risk is mixed, with data mostly from developed countries, and aggregated risk measures are used in the study of this relation in the existing literature. The purpose of this study is to examine how managerial ability affects idiosyncratic risk taking, especially in innovative firms in China, which is the largest developing country in the world. Using Demerjian et~al.'s (2012) measure of managerial ability and a sample of Chinese firms from 2009 to 2019, we observe a positive relationship between managerial ability and idiosyncratic risk based on fixed effects models. The findings are robust to endogeneity concerns. Subsample analyses reveal that the positive relation between managers and idiosyncratic risk is more pronounced when there is greater earnings pressure and or when there are information gaps, whereas such a positive relation is less pronounced at higher innovation levels due to less earning pressure in the short run and a greater focus on long-term growth through technological innovation. In addition, we find that managerial ability has a positive impact on firm value, yet this positive effect is weakened with higher levels of idiosyncratic fluctuation. Our study has implications for agency theory in that managerial ability, which may come with additional agency problems and heterogeneous risk-taking incentives, can have a negative impact on firm value if the able managers' risk-taking motivations and behaviors are not adequately monitored or constrained.
Keywords: 650; Earnings pressure; Firm innovation; Idiosyncratic risk; Information asymmetry; Managerial ability